Edukasi dan Implementasi Teknik Relaksasi Benson dalam Menurunkan Skala Nyeri pada Pasien Post Operasi Sectio Caesarea - Mohammad Ilham Riziq Muzaki; Dwi Novitasari; Atun Raudotul Ma'rifah; Awal Tunis Yantoro (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Over time, the need for cesarean sections for pregnant women is increasing. Patients who have undergone surgery often experience common problems when they are hospitalized after surgery. Postoperative pain is one of the most common postoperativ e problems. One non -pharmacological method for managing pain is the Benson relaxation technique. Objective: This Community Service (PkM) aims to reduce pain in post -cesarean section patients using the Benson Relaxation Technique. Method: The Benson relaxat ion technique was applied directly twice for 15 minutes, two hours after surgery, as part of the community service activity. The Numerical Rating Scale (NRS) was used to measure pain. The target audience of this PkM was 30 post -operative patients at RSI Purwokerto who experienced pain. Results. Before the intervention, the average pain score was in the moderate range (4.9), and after the intervention, the average pain score was in the mild range (2.3). This was demonstrated by the PkM exercise. 2.13 is the average reduction in pain. Conclusion: The results of this Community Service (PKM) exercise indicate that postoperative pain can be reduced using Benson relaxation.